(NsOWREMENNYJ RUSSKIJ QZYK (B:s (NlEKSIKOLOGIQ (B: (Nu^EBOE POSOBIE (B/s - (NfOMINA(B, (NmARGARITA iWANOWNAs ((NmOSKWA (B:s (NwYS[AQ [KOLA(B,s, 1978)
(NuKAZ(B. (NPREDM(B. (NI IMEN(B.: (NS(B. 252-254s
Keywords: (NrUSSKIJ QZYKs -- (NlEKSIKOLOGIQs